Current management of hemorrhage from severe pelvic fractures: Results of an American Association for the Surgery of Trauma multi-institutional trial. Issue 5 (May 2016) - Costantini, Todd W.; Coimbra, Raul; Holcomb, John B.; Podbielski, Jeanette M.; Catalano, Richard; Blackburn, Allie; Scalea, Thomas M.; Stein, Deborah M.; Williams, Lashonda; Conflitti, Joseph; Keeney, Scott; Suleiman, Ghada; et al.
Abstract : BACKGROUND: There is no consensus as to the optimal treatment paradigm for patients presenting with hemorrhage from severe pelvic fracture. This study was established to determine the methods of hemorrhage control currently being used in clinical practice. METHODS: This prospective, observational multi-center study enrolled patients with pelvic fracture from blunt trauma. Demographic data, admission vital signs, presence of shock on admission (systolic blood pressure < 90 mm Hg or heart rate > 120 beats per minute or base deficit < −5), method of hemorrhage control, transfusion requirements, and outcome were collected. RESULTS: A total of 1, 339 patients with pelvic fracture were enrolled from 11 Level I trauma centers. Fifty-seven percent of the patients were male, with a mean ± SD age of 47.1 ± 21.6 years, and Injury Severity Score (ISS) of 19.2 ± 12.7. In-hospital mortality was 9.0 %. Angioembolization and external fixator placement were the most common method of hemorrhage control used. A total of 128 patients (9.6%) underwent diagnostic angiography with contrast extravasation noted in 63 patients. Therapeutic angioembolization was performed on 79 patients (5.9%). There were 178 patients (13.3%) with pelvic fracture admitted in shock with a mean ± SD ISS of 28.2 ± 14.1. In the shock group, 44 patients (24.7%) underwent angiography to diagnose a pelvic source of bleeding with contrast extravasation found in 27 patients. Thirty patients (16.9%) were treated with therapeutic angioembolization. Resuscitative endovascular balloon occlusion of the aorta was performed on five patients in shock and used by only one of the participating centers. Mortality was 32.0% for patients with pelvic fracture admitted in shock. CONCLUSION: Patients with pelvic fracture admitted in shock have high mortality. Several methods were used for hemorrhage control with significant variation across institutions. The use of resuscitative endovascular balloon occlusion of the aorta may prove to be an important adjunct in the treatment of patients with severe pelvic fracture in shock; however, it is in the early stages of evaluation and not currently used widely across trauma centers. LEVEL OF EVIDENCE: Prognostic study, level II; therapeutic study, level III.